Digital Literacy Education in Welsh Primary and Secondary Schools from the 1960s to the Present - SARAH WILLIAMS (2023)
Digital technologies are imbued with ideologies that impact culture and society. These technologies are ubiquitous, pervasive, and central to how people communicate, consume information, and orchestrate their lives. Therefore, for people to fully understand the impact and influence of these technologies on their lives and engage with them and the digital environment in a critically informed way - digital literacy is an absolute and necessary requirement. However, we are not seeing digital literacy as standard. This study assesses: (1) Whether students are being sufficiently educated about how digital technologies use and affect them in a social, cultural, and ethical capacity; (2) Whether the programme content of digital literacy education (DLE) is primarily driven by neo-liberal economically driven government policies; and (3) How much influence private neo-liberal capitalistic enterprises have in determining the educational agenda of DLE? Qualitative data was collected via three focus group interviews and twenty-six semi-structured interviews which explored students, educational professionals, and government officials’ views of DLE in Wales. The data was thematically coded using critical discourse analysis, and analysed using theories developed in Herbert Marcuse’s 1964 publication One-Dimensional Man. The results indicated that DLE educational policy has broadened to include knowledge that extends beyond the teaching of purely mechanistic skills. However, a variety of factors were identified that impede their implementation. Additionally, it is argued that students’ mechanistic digital skills have been declining since the introduction of touch screen technologies into primary and secondary schools. Findings also indicated that educators main DLE focus was on preparing students for employment purposes, and the influence private neo-liberal capitalistic enterprises have in determining not only the educational agenda of DLE, but education in general is profound, and has accelerated exponentially since the COVID-19 imposed lockdowns.